Hospitality and Tourism Education in Uganda: An Integrative Analysis of Students’ Motivations and Industry Perceptions - Tukamushaba, Eddy K.; Xiao, Honggen (Journal of teaching in travel & tourism, 2012)
This article presents an integrative analysis of students’ motivations in choosing hospitality and tourism programs as well as industry perceptions of graduates’ qualifications for employment in Uganda. A mixed-method approach is used for data collection, analysis, and reporting. Quantitatively, the study replicates a motivational scale of choosing educational programs and identifies six factors that collectively explain about 60% of the variance in students choosing hospitality and tourism programs in this African developing economy. Industry perceptions of graduates’ qualifications for employment are reported on the basis of qualitative interviews. Implications of the study are discussed in light of curriculum and program refinement to better prepare future graduates for the industry.
Keywords: hospitality and tourism education; study motivation; career choice